Manajemen Risiko pada Rencana Pengamanan Air Minum (RPAM) Operator untuk Sumber Air Permukaan PDAM Krueng Peusangan Kabupaten Bireuen - Chakila (ITB Journal Publisher, LPPM ITB, 2022)
Perusahaan Daerah Air Minum (PDAM) Krueng Peusangan uses water from Krueng Peusangan as its source of raw water. Krueng Peusangan water quality monitoring was carried out by BAPEDAL Aceh in 2016 and the first period was classified into